Corrective Effect of Verbascoside on Histomorphological Differences and Oxidative Stress in Colon Mucosa of Rats in Which Colon Ischemia–Reperfusion Injury was Induced - Değer, Ayşe Nur; Özyiğit, Filiz; Koçak, Fatma Emel; Bayhan, Zülfü; Zeren, Sezgin; Arık, Özlem; Değer, Hakkı (Turkish Journal of Gastroenterology, 2021)
Background: This study aims to show the corrective effect of verbascoside on histomorphological and biochemical differences in the colon mucosa of rats in which colon ischemia–reperfusion (I/R) injury was induced. Methods: Fifty Sprague Dawley male rats were divided into 5 groups, of control, sham, ischemia (I), I/R, and I/R+verbascoside. Ischemia and reperfusion were applied to the suitable groups for 30 minutes and 120 minutes respectively, and 10 mg/kg verbascoside was administered intraperitoneally. Histomorphological assessment was done in the colon tissues obtained, and the goblet cells were assessed using the Alcian blue method. Proliferating cell nuclear antigen (PCNA), TUNEL, and hypoxia-induced factor 1 (HIF-1α) assays were used to assess oxidative stress with the immunohistochemical method. Malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), and total thiol (TT) levels were checked, for a biochemical analysis of oxidative stress. Results: Compared with the I/R group, histomorphological differences were seen to be corrected in colon epithelium in the I/ R+verbascoside group. The goblet cell number increased and cell proliferation was increased, as seen with the PCNA assay; and apoptosis was decreased, as seen with the TUNEL assay. HIF-1α expression also decreased in the drug group. In the drug group, SOD, GSH-Px, TAS, and TT levels increased, but TOS, OSI, and MDA levels decreased. Conclusion: It was seen that verbascoside had a corrective effect on histomorphological and biochemical differences caused by I/R injury.